Frequency-dependent gating of synaptic transmission and plasticity by dopamine - Ito, Hiroshi T.; Schuman, Erin M. (Frontiers in Neural Circuits, 2007)
The neurotransmitter dopamine (DA) plays an important role in learning by enhancing the saliency of behaviorally relevant stimuli. How this stimulus selection is achieved on the cellular level, however, is not known. Here, in recordings from hippocampal slices, we show that DA acts specifically at the direct cortical input to hippocampal area CA1 (the temporoammonic (TA) pathway) to filter the excitatory drive onto pyramidal neurons based on the input frequency. During low-frequency patterns of stimulation, DA depressed excitatory TA inputs to both CA1 pyramidal neurons and local inhibitory GABAergic interneurons via presynaptic inhibition. In contrast, during high-frequency patterns of stimulation, DA potently facilitated the TA excitatory drive onto CA1 pyramidal neurons, owing to diminished feedforward inhibition. Analysis of DA's effects over a broad range of stimulus frequencies indicates that it acts as a high-pass filter, augmenting the response to high-frequency inputs while diminishing the impact of low-frequency inputs. These modulatory effects of DA exert a profound influence on activity-dependent forms of synaptic plasticity at both TA-CA1 and Schaffer-collateral (SC)-CA1 synapses. Taken together, our data demonstrate that DA acts as a gate on the direct cortical input to the hippocampus, modulating information flow and synaptic plasticity in a frequency-dependent manner.